Teknik Identifikasi Ektoparasit Ikan Brek (Puntius orphoides) yang Ditemukan di Sungai Cimanuk Kabupaten Sumedang - Asep Rachmat Pratama; Nurul Ekawati; Billy Rifa Kusumah (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
Brek fish is one of the economically consumed fish that is affordable. In Indonesia, brek fish have long been cultivated because they are suitable for tropical climates, so they can be cultivated throughout the year. The purpose of this study was to determine the types of ectoparasites as well as the intensity and prevalence values carried out at the Cimanuk River, Sumedang Regency. Based on the results of the study, 6 types of ectoparasites were found in brek fish, namely Trichodina sp., Dactylogyrus sp., Gyrodactylus sp., Oodinium sp., Ichthyophthirius multifiliis and Myxobolus sp. The prevalence rate for Trichodina sp. 66.7% and the intensity value is 7 ind/head, the prevalence value of Dactylogyrus sp. 53.3% and an intensity value of 2.8 ind/head, the prevalence value of Gyrodactylus sp. 33.3% and an intensity value of 2.4 ind/head, a prevalence value of Ichthyophthirius multifiliis 46.6% and an intensity value of 2.6 ind/head, a prevalence value of Myxobolus sp. 16.6% and the intensity value of 0.8 ind/head and the prevalence value of Oodinium sp. 23.3% and an intensity value of 1.6 ind/head.